Obtaining of Carbide Strengthening Diffusion Layers of the Given Properties on the Surface of High-Chromium Steel - N. G. Koukhareva; S. N. Petrovich; N. A. Galynskaya; K. N. Mashkov; M. N. Moukha (Наука и техника)
The paper shows theoretical substantiated possibility to obtain high-quality carbide strengthening diffusion layers on the surface of high-chromium steel and the fields of their practical application.